Determinants of Stock Investment Decision Making: A Study on Investors in Indonesia - Sari, Ratna; Kusnanto, K.; Aswindo, Munarni (Manunggal Halim Jaya, 2022)
This study aims to understand the determinants of stock investment decision making by investors in the Indonesian stock market. Mixed methods are used by combining quantitative data from surveys and qualitative data from interviews. A survey was conducted among 400 investors using an online questionnaire, while interviews were conducted with selected investors. The results show that fundamental analysis plays an important role in stock investment decision-making. In addition, market sentiment and herd behavior also influence investment decisions. Investors also have different risk tolerances depending on investment objectives and personal risk profiles. This research provides insights for investors and professionals in the Indonesian stock market to develop more prudent and data-driven investment strategies.